Delivering patient-centered care in Parkinson's disease: Challenges and consensus from an international panel. (March 2020) - Bhidayasiri, Roongroj; Panyakaew, Pattamon; Trenkwalder, Claudia; Jeon, Beomseok; Hattori, Nobutaka; Jagota, Priya; Wu, Yih-Ru; Moro, Elena; Lim, Shen-Yang; Shang, Huifang; Rosales, Raymond; Lee, Jee-Young; et al.
Abstract: An international panel of movement disorders specialists explored the views and perceptions of people with Parkinson's disease (PD) about their condition and its treatment, including the potential mismatch between the clinician's view of the patient's condition and their own view of what aspects of the disease most affect their daily lives. The initiative was focused on Asian countries, so participants comprised experts in the management of PD from key centers in Asia, with additional insight provided by European and the North American movement disorders experts. Analysis of peer-reviewed publications on patient perceptions of PD and the factors that they consider important to their wellbeing identified several contributing factors to the mismatch of views, including gaps in knowledge of PD and its treatment, an understanding of the clinical heterogeneity of PD, and the importance of a multidisciplinary approach to patient care. The faculty proposed options to bridge these gaps to ensure that PD patients receive the personalized treatment they need to achieve the best possible outcomes. It was considered essential to improve patient knowledge about PD and its treatment, as well as increasing the awareness of clinicians of PD heterogeneity in presentation and treatment response. A multidisciplinary and shared-care approach to PD was needed alongside the use of patient-centered outcome measures in clinical trials and clinical practice to better capture the patient experience and improve the delivery of individualized therapy. Highlights: This is a report of a consensus meeting of movement disorder specialists from Asia, Europe and the North America. There is a clear disconnect between clinicians' versus patients' perceptions about Parkinson's disease. Knowledge gaps, lack of patient-centered outcomes, and multidisciplinary care are factors contributing to the disconnect. Addressing these factors will be key to providing personalized medicine and, thereby, improving care in PD.